Feasibility of tracking invasive Escherichia coli disease among older adults in a community setting: A prospective observational study - Joachim Doua; Miquel Ekkelenkamp; Theo Verheij; Oscar Go; Stephen Ruhmel; Kimberly Leathers; Bart Spiessens; Sanne van Rooij; Vance G. Fowler; Jeroen Geurtsen; Rowena Dolor; Michal Sarnecki; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose Invasive Escherichia coli disease (IED) encompasses a diverse range of sterile site infections. This study evaluated the feasibility of capturing IED among community-dwelling older adults to inform the implementation of a phase 3 efficacy trial of a novel vaccine against IED (NCT04899336). Methods EXPECT-1 (NCT04087681) was a prospective, multinational, observational study conducted in medically stable participants aged ≥ 60 years. At least 50% of participants were selected based on a history of urinary tract infection (UTI) in the previous 10 years. The main outcomes were the incidence of IED and the number of hospitalisations reported by the site vs participant. The length of follow-up was 12 months. In a US-based substudy, a smartphone-based geofencing was evaluated to track hospital entries. Results In total, 4470 participants were enrolled (median age, 70.0 years); 59.5% (2657/4469) of participants had a history of UTI in the previous 10 years. Four IED events were captured through deployment of different tracking methods: a self-report, a general practitioner (GP) report, and a follow-up call. The incidence rate of IED was 98.6 events per 100,000 person-years. The number of reported hospitalisations was 2529/4470 (56.6%) by the site and 2177/4470 (48.7%) by participants; 13.8% of hospitalisations would have been missed if utilising only site reports. Geofencing detected 72 hospital entries. Conclusion Deployment of multiple tracking methods can optimise detection of IED among community-dwelling older adults. Older adults with a history of UTI could be feasibly targeted for a phase 3 vaccine efficacy trial through a network of GPs.

Matching the proteome to the genome: the microbody of penicillin-producing Penicillium chrysogenum cells - Jan A. K. W. Kiel; Marco A. van den Berg; Fabrizia Fusetti; Bert Poolman; Roel A. L. Bovenberg; Marten Veenhuis; Ida J. van der Klei (Functional & Integrative Genomics, 2009)

Response of Neisseria meningitidis to iron limitation - Annika Pettersson; Jan T. Poolman; Peter van der Ley; Jan Tommassen (Antonie van Leeuwenhoek, 1997)

Editorial - Jan T. Poolman (Antonie van Leeuwenhoek, 1987)